Self-Efficacy dan Burnout pada Perawat Rumah Sakit Umum Daerah (RSUD) Kanjeng Raden Mas Tumenggung (KRMT) Wongsonegoro Semarang di Masa Pandemi Covid-19 - Sarah Cinthya Arif; Sutarto Wijono (Kuras Institute, 2022)
During the Covid-19 pandemic, nurses felt an increase in their perceived workload. Often the nurses feel exhaustion after doing work. The purpose of this study was to determine the relationship between self-efficacy and burnout in nurses at RSUD K.R.M.T. Wongsonegoro Semarang during the Covid-19 pandemic. Participants in this study were female or male nurses at RSUD K.R.M.T. Wongsonegoro Semarang who became the implementing nurse in the isolation room during the Covid-19 pandemic, totaling 34 participants. Sampling uses a saturation sampling technique, which is a sampling technique where all members of the population are used as samples, this is done if the population is relatively small, less than 30, or the research wants to make generalizations with very small errors (Sugiyono, 2017). Research variables were measured using two scales, namely the General Self-Efficacy scale compiled by Schwarzer and Jerusalem (1995) used to measure self-efficacy, and the burnout scale used was the Maslach Burnout Inventory-Human Services Survey (MBI-HSS) Scale which measures burnout by adjusting the target subjects involved with human services such as nurses compiled by Malsach & Jackson (in Ibtissam, 2012). The scale is distributed using googleform. Based on the results of the study, the correlation coefficient (r) = -0.677 with a sig value of 0.000 (p <0.05) means that there is a negative relationship between self-efficacy and burnout in nurses at K.R.M.T Hospital. Wongsonegoro Semarang. It means that the higher of burnout experienced then the lower of self-efficacy, otherwise the lower of burnout experienced by nurses at the hospital so they have the higher of self-efficacy.